Kata Kerja Transitif dan Intransitif dalam Bahasa Arab dan Bahasa Indonesia (Studi Linguistik Kontrastif) - Izzudin Mustafa; Tubagus Kesa Purwasandy; Isop Syafe'i (Universitas Yudharta Pasuruan, 2020)
This research aims to determine contrastive linguistic, transitive dan intransitive verb in arabic language and Indonesian language, and to determine similarities and differences between both of them. This research uses descriptive analytic method with contrastive linguistic approach. Subject of this research is contrastive linguistic contrastive theory and transitive and intransitive verb. Data collection technique is carried out through documentation studies, while the data analysis technique is done by selecting the data obtained, then collected for analysis and conclusions. The results of this research are the contrastive linguistic is method for analyzing language to find similarities and differences in order to find principles that can be applied practically. In Arabic and Indonesian language, transitive verb is verb that has objects and complement, while intransitive verb is verb that does not have objects and complement. The equation between the two is that both languages have one-object and two-object transitive verb, while the difference is that Indonesian has semitransitive sentence type but Arabic language does not have, Arabic language has three-object verb but Indonesian language does not have, Arabic language has different between transitive verb and preposition but Indonesian language does not have.